2020
DOI: 10.1038/s41598-020-76474-8
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota and metabolic health among overweight and obese individuals

Abstract: Although obesity is associated with numerous diseases, the risks of disease may depend on metabolic health. Associations between the gut microbiota, obesity, and metabolic syndrome have been reported, but differences in microbiomes according to metabolic health in the obese population have not been explored in previous studies. Here, we investigated the composition of gut microbiota according to metabolic health status in obese and overweight subjects. A total of 747 overweight or obese adults were categorized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
84
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(93 citation statements)
references
References 53 publications
6
84
2
1
Order By: Relevance
“…Interestingly, members of the Parabacteroides family, such as Parabacteroides goldsteinii ( 48 ) and Parabacteroides distasonis ( 49 ), are promising probiotics that could alleviate obesity and obesity-associated metabolic dysfunctions. However, it was reported that Oscillospira was associated with leanness or lower BMI and was significantly more abundant in metabolically healthy participants who were overweight or obese ( 50 ). One study showed that members of the Oscillospira genus are highly heritable and positively associated with the leanness-promoting bacterial species Christensenella minuta .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, members of the Parabacteroides family, such as Parabacteroides goldsteinii ( 48 ) and Parabacteroides distasonis ( 49 ), are promising probiotics that could alleviate obesity and obesity-associated metabolic dysfunctions. However, it was reported that Oscillospira was associated with leanness or lower BMI and was significantly more abundant in metabolically healthy participants who were overweight or obese ( 50 ). One study showed that members of the Oscillospira genus are highly heritable and positively associated with the leanness-promoting bacterial species Christensenella minuta .…”
Section: Discussionmentioning
confidence: 99%
“…Some Oscillospira species likely could secrete important short-chain fatty acids (SCFAs), which are beneficial for body weight control as well as glucose and lipid homeostasis ( 44 ). Another possible reason for the association between Oscillospira and leanness was that Oscillospira may be able to degrade host glycans and thus help hosts spend metabolic energy to regenerate degraded glycoproteins ( 50 ). In this regard, we speculated that the increased abundance of Porphyromonadaceae Parabacteroides and Ruminococcaceae Oscillospira in this study may be a response of gut microbiota to dietary intervention, assisting in weight loss in the LCD.…”
Section: Discussionmentioning
confidence: 99%
“…Some alterations in the gut microbiota are associated with an increased energy harvest from diet, low-grade inflammation, and altered adipose tissue composition ( Pihl et al., 2016 ).These processes are considered the link between gut microbiota, O, and metabolic syndrome ( Bouter et al., 2017 ). Several studies demonstrated microbiota alterations in O and obesity with metabolic syndrome (OMS) using 16S profiling ( Bai et al., 2019 ; Chen et al., 2020 ; Gallardo-Becerra et al., 2020 ; Kim et al., 2020 ) and metatranscriptomic approaches ( Gallardo-Becerra et al., 2020 ). It has been observed that dietary intervention was associated with changes in the virome community, in which individuals on the same diet converged ( Minot et al., 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…To date, only a few research groups have investigated the association between gut microbiota and the MHO phenotype. Kim et al [ 76 ] profiled fecal microbiota from over 700 overweight and obese Korean individuals who had no metabolic abnormality (metabolically healthy) or had at least one metabolic abnormality (metabolically unhealthy). To define metabolic abnormalities the NCEP ATP III criteria were used.…”
Section: Microbiomementioning
confidence: 99%